Resistance of three grapevine cultivars to Grape Erineum Mite, Colomerus vitis (Acari: Eriophyidae), in field conditions - Saeid Javadi Khederi; Mohammad Khanjani; Bahman Asali Fayaz (Persian Journal of Acarology)
The Grape Erineum Mite (GEM), Colomerus vitis (Pagenstecher) (Acari: Eriophyidae), is a serious pest of vine (Vitis vinifera L.) in western Iran. Host plant resistance has not been explored as a method for its Integrated Mite Management.  In this study, GEM-vine interactions and the biochemical features potentially related to vine resistance/ sensitiveness have been investigated on Fakhri, Gazne and White Thompson seedless cultivated in field conditions in western Iran. The lowest and highest mite densities were found on leaves of White Thompson Seedless and Gazne, respectively. As expected, reduction of healthy leaf area, increase of leaf weight, shortening of shoots and erinea formation were more relevant on the most infested Gazne; White Thompson Seedless appeared to be affected by GEM infestation. The diameter of grape berries and their weight did not differ significantly between infested and control plants on all cultivars. Mite density appeared to be negatively related to the sugar content only for Gazne grape. The amount of the leaf waxes was highest in White Thompson Seedless on which the lowest mite density, the lowest percentage of erinea and largest healthy leaf areas were detected. Carbohydrate content of leaves was the lowest on the least mite-infested Thomson seedless and the highest on the most infested Gazne, while phenols decreased in Gazne after mite infestation.